Tel1 and Rif2 oppositely regulate telomere protection at uncapped telomeres in Saccharomyces cerevisiae. (20th September 2018) - Zhang, Ling-Li; Wu, Zhenfang; Zhou, Jin-Qiu
Abstract: It has been well documented that Tel1 positively regulates telomere-end resection by promoting Mre11-Rad50-Xrs2 (MRX) activity, while Rif2 negatively regulates telomere-end resection by inhibiting MRX activity. At uncapped telomeres, whether Tel1 or Rif2 plays any role remains largely unknown. In this work, we examined the roles of Tel1 and Rif2 at uncapped telomeres in yku70 Δ and/or cdc13-1 mutant cells cultured at non-permissive temperature. We found that deletion of TEL1 exacerbates the temperature sensitivity of both yku70 Δ and cdc13-1  cells. Further epistasis analysis indicated that MRX and Tel1 function in the same pathway in telomere protection. Consistently, TEL1 deletion increases accumulation of Exo1-dependent telomeric single-stranded DNA (ssDNA) at uncapped telomeres, which stimulates checkpoint-dependent cell cycle arrest. Moreover, TEL1 deletion in yku70 Δ cells facilitates Rad51-dependent Y′ recombination. In contrast, RIF2 deletion in yku70 Δ cells decreases the accumulation of telomeric ssDNA after 8 h of incubation at the non-permissive temperature of 37 °C and suppresses the temperature sensitivity of yku70 Δ cells, likely due to the increase of Mre11 association at telomeres. Collectively, our findings indicate that Tel1 and Rif2 regulate telomere protection at uncapped telomeres via their roles in balancing MRX activity in telomere resection.